HORUS - High Operational Reliability For Unmanned Systems - Figuet, B.; Leibundgut, P.; Pedrioli, A.; Frauenfelder, A.; Doran, H.; Capone, P. (My University, 2022)
In an effort to increase Unmanned Aerial Vehicles (UAV) mission safety and reliability, this paper introduces the HORUS prototype. HORUS is a small hardware device that allows UAVs to be flown with two Commercial Off The Shelf (COTS) Flight Control Units (FCU) instead of a single one traditionally. The HORUS device offers the possibility to manually switch from one FCU to the other but also to switch autonomously if the UAV gets out of the allowed geographic boundaries or out of its defined flight envelope. Although envelope protection or geofencing features are commonly available on COTS FCUs, they are generally not robust to sensor or FCU failures. But, as a result of its design, which has been developed following manned aviation safety process guidelines, the HORUS device offers high reliability and integrity. In this context, the main objective of this paper is to introduce the HORUS concept, to describe the software and hardware architectures and to demonstrate its functionality by showing some flight test results.